2018
DOI: 10.5114/ada.2018.75609
|View full text |Cite
|
Sign up to set email alerts
|

Decreased blood CD4+PD-1+ and CD8+PD-1+ T cells in psoriatic patients with and without arthritis

Abstract: IntroductionPsoriasis with and without arthritis have common immunological mechanisms which among others involve the interactions between cytokines produced by T cells, including Th1, Th17 and Th22. Although quite a lot is known about psoriasis pathogenesis, the cause of chronic immune activation and response in the disease remains unclear. One of the negative regulators of the immune system is programmed death 1 (PD-1).AimTo assess the expression level of PD-1 in the peripheral T cells of psoriatic patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
2
14
2
Order By: Relevance
“…In our present study, the circulating sNRP-1 was significantly higher in psoriatic patients in comparison to the controls, whereas in one of our earlier studies, the expression of NRP-1 mRNA in peripheral blood mononuclear cells (PBMCs) was significantly downregulated in psoriatic patients, both with and without arthritis [21]. Therefore, the increased sNRP-1 concentrations observed in our psoriatic patients could be regarded as a negative feedback mechanism in the process of neovascularization, on the one hand, but, on the other hand, they could also be seen as an immune tolerance compromising factor.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our present study, the circulating sNRP-1 was significantly higher in psoriatic patients in comparison to the controls, whereas in one of our earlier studies, the expression of NRP-1 mRNA in peripheral blood mononuclear cells (PBMCs) was significantly downregulated in psoriatic patients, both with and without arthritis [21]. Therefore, the increased sNRP-1 concentrations observed in our psoriatic patients could be regarded as a negative feedback mechanism in the process of neovascularization, on the one hand, but, on the other hand, they could also be seen as an immune tolerance compromising factor.…”
Section: Discussioncontrasting
confidence: 52%
“…The soluble form of PD-1, however, acts as a decoy receptor able to bind and neutralize PD-1/PDL1 [4, 5]. In our recent studies we have found that both the expression of PDCD1 mRNA in peripheral blood mononuclear cells [20] and the expression of PD-1 protein on CD4+ and CD8+ T cells were significantly decreased in psoriatic patients both with and without arthritis [21]. Thus, the compromised PD-1 function on CD4 + and CD8+ T cells might indicate inappropriate activation status and suggest dysregulation of the immune suppression mechanisms, which may lead to abnormal, persistent T cell activation and cytokine production in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PD-1 expression is absent on OA synovial T cells, suggesting its expression may be involved in IA pathogenesis rather than merely a consequence of inflammation [ 70 ]. Within the periphery, a decrease in the percentage of circulating CD4 + and CD8 + PD-1 + cells in the blood of PsA and RA patients, respectively, has also been reported [ 71 , 72 ]. In the context of myeloid cells, PD-L1 is expressed on synovial fluid CD1c + dendritic cells [ 68 ], in addition to synovial fluid macrophages [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and effective treatment protect patients from complications and severe consequences of the musculoskeletal system. In order to understand the exact etiopathogenesis of this disease, its early detection and effective treatment, various biomarkers specific to this disease are investigated [1,[4][5][6][7][8]. According to the National Institutes of Health Biomarkers Definitions Working Group, a biomarker is "a characteristic that is objectively measured and evaluated as an indicator of normal biological processes, pathogenic processes, or pharmacologic responses to therapeutic intervention" [9].…”
Section: Introductionmentioning
confidence: 99%